2020
DOI: 10.1101/2020.01.31.928234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stress specific impact of ALKBH1 on tRNA cleavage and tiRNA generation

Abstract: tiRNAs are small non-coding RNAs produced when tRNA is cleaved under stress. tRNA methylation modifications has emerged in recent years as important regulators for tRNA structural stability and sensitivity to cleavage and tiRNA generation during stress, however, the specificity and higher regulation of such a process is not fully understood. Alkbh1 is a m 1 A demethylase that leads to destabilization of tRNA and enhanced tRNA cleavage. We examined the impact of Alkbh1 targeting via gene knockdown or overexpres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 31 publications
(25 reference statements)
2
17
0
Order By: Relevance
“…Although previous studies showed that the production of tiRNAs is closely related to ANG [27,36,37], a recent study verified that the production of tiRNA is not completely dependent on ANG, suggesting there are other RNases that produce tiRNAs [38]. Moreover, mature tRNA has a lot of base modifications, such as m5C, m1A, m3C, and Ψ (Pseudouridylation), which can protect tRNAs from cleavage [39][40][41][42][43]. It is also essential to understand the intrinsic and extrinsic factors that participate in the production of tsRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies showed that the production of tiRNAs is closely related to ANG [27,36,37], a recent study verified that the production of tiRNA is not completely dependent on ANG, suggesting there are other RNases that produce tiRNAs [38]. Moreover, mature tRNA has a lot of base modifications, such as m5C, m1A, m3C, and Ψ (Pseudouridylation), which can protect tRNAs from cleavage [39][40][41][42][43]. It is also essential to understand the intrinsic and extrinsic factors that participate in the production of tsRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have identified Ang‐independent cleavage (Y. Akiyama et al, 2019; Krishna et al, 2019; Su et al, 2019). In addition, we observed in our previous report the existence of larger 5ʹ tiRNA fragments implying cleavage away from the anticodon site (i.e., noncanonical cleavage; Rashad, Han, et al, 2020). The exact role of these noncanonical fragments is not yet known, as well as their regulation and cleavage patterns.…”
Section: Introductionmentioning
confidence: 63%
“…The same process was shown to drive metastasis in breast cancer (Goodarzi et al, 2015). tRNA modifications play an important role in regulating transcript availability and efficient protein translation (Liu et al, 2016; Pollo‐Oliveira et al, 2020) and can impact cellular stress response (Rashad, Han, et al, 2020) and cancer biology (Rossello‐Tortella et al, 2020). tRNA is also a source of small noncoding RNAs that have an important regulatory role in translation, namely, tiRNAs and tRFs (tRNA‐derived fragments produced via DICER; Ivanov et al, 2011; Rashad, Niizuma, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations